2006
DOI: 10.1002/marc.200600314
|View full text |Cite
|
Sign up to set email alerts
|

Thienopyrazine‐Based Low‐Bandgap Poly(heteroaryleneethynylene)s for Photovoltaic Devices

Abstract: Summary: Low‐bandgap π‐conjugated polymers that consist of alkyl thiophene/alkoxy phenylene and 2,3‐diphenylthieno[3,4‐b]pyrazine units have been prepared in high yields by a Sonogashira polycondensation. The copolymers are characterized by NMR, IR, UV, GPC, and elemental analysis. Thin films of the polymers P1, P2, and P3 exhibit an optical bandgap of ≈1.57–1.60 eV. Under simulated AM 1.5 conditions P2/PCBM devices on polyester foil provide a short circuit current of ISC = 10.72 mA · cm−2, an open circuit vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 33 publications
1
93
0
Order By: Relevance
“…Such E p,a values afford an approximate estimation of the HOMO energy levels for the five molecules (also reported in Table 3) by use of Equation (1): [17,18] E HOMO ½eV % À1eðE p,a ½V vs: Fc þ jFc þ 4:8 ½V Fc þ jFc vs: zeroÞ ð1Þ ultimately based on the absolute value for the normal hydrogen electrode (NHE) critically assessed in a fundamental review paper. [19] More significant, albeit moderate, appears the positive shift of the first reduction peak potentials, E p,c , with increasing n a .…”
Section: Electrochemical Properties Of T'xmentioning
confidence: 99%
“…Such E p,a values afford an approximate estimation of the HOMO energy levels for the five molecules (also reported in Table 3) by use of Equation (1): [17,18] E HOMO ½eV % À1eðE p,a ½V vs: Fc þ jFc þ 4:8 ½V Fc þ jFc vs: zeroÞ ð1Þ ultimately based on the absolute value for the normal hydrogen electrode (NHE) critically assessed in a fundamental review paper. [19] More significant, albeit moderate, appears the positive shift of the first reduction peak potentials, E p,c , with increasing n a .…”
Section: Electrochemical Properties Of T'xmentioning
confidence: 99%
“…From the first oxidation and reduction peak potentials, values of HOMO and LUMO levels can be estimated by the following equations [72,73] ultimately based on the absolute value for the normal hydrogen electrode (NHE) critically assessed in a fundamental review paper: [74] E HOMO (eV) » -1e ´ [ (E p,a (V vs Fc + |Fc) + 4.8 (V Fc + |Fc vs zero)]…”
Section: Electrochemical Homo and Lumo Levels And Gapsmentioning
confidence: 99%
“…Although it is impossible to obtain a precise discussion due to the presence of irreversible redox waves, as shown in Table 3, the HOMOLUMO gaps of the three molecules, estimated from the onsets of the oxidation and the reduction peaks, indicated the similarity between 1 and 5 (¦E CV : 2.82 eV for 1, 2.81 eV for 5, and 3.41 eV for 6, respectively). 10 These results indicated that electrochemical and optical properties of the C 70 fragment 1 are also largely affected by the indenopyrene 5 skeleton rather than benzo [e]pyrene 6 skeleton.…”
Section: ¹1mentioning
confidence: 87%